The Effect of Combined Benson Relaxation and Warm Compress Therapy on Reducing Dysmenorrhea Pain Among Adolescents - Utami, Dwi; Sunaryo, Tri; Rohimah, Yeni Tutu (Interest : Jurnal Ilmu Kesehatan, 2024)
Background: Dysmenorrhoea is pain felt before or during menstruation, characterised by abdominal cramps that can radiate to the back. Nonpharmacological interventions such as Benson relaxation and warm compresses are effective first aid to reduce dysmenorrhoea pain. This study aims to analyse the effect of a combination of Benson relaxation and warm compresses on reducing dysmenorrhoea pain in adolescents.  Methods: This study used a quasi-experimental design with a pre-posttest control group design. A total of 60 adolescents were selected through purposive sampling technique and divided into two groups: intervention group (n=30) who received combination therapy of Benson relaxation and warm compress, and control group (n=30) who only received warm compress. Pain levels were measured using the Numeric Rating Scale (NRS), and data were analysed using the Wilcoxon test.  Results: There was a decrease in pain levels in both groups after the intervention, with a more noticeable decrease in the intervention group (mean difference = 0.8) compared to the control group (mean difference = 0.4). However, the Wilcoxon test results showed a p value = 0.542 which means there was no statistically significant difference between the two groups.  Conclusions: Warm compress therapy or a combination of warm compress with Benson relaxation is equally effective in reducing dysmenorrhoea pain in adolescents. Both interventions can be applied as non-pharmacological interventions in the school environment as part of promotive and preventive efforts against dysmenorrhoea pain in adolescents.